Exergy assessment and energy integration of advanced gas turbine cycles on an offshore petroleum production platform. (1st October 2019) - Nascimento Silva, Fernanda Cristina; Flórez-Orrego, Daniel; de Oliveira Junior, Silvio
Highlights: Conventional configuration presents power efficiency of 28.98%, followed by S-Graz with 27.10%. S-Graz configuration presents the best CO2 mitigation potential with only 0.014 kgCO2 /toil . CO2 emissions costs for oil and gas increase by nearly two to nine fold for the conventional configuration. Although advanced configurations are able to mitigate CO2, 6–7% additional fuel is still required. The amines-based configuration has the largest fuel consumption and energy destruction among all three plants. Abstract: On offshore platform applications, power and heat are normally supplied by simple open cycle gas turbine (OCGT) and heat recovery steam generators (HRSG) at lower efficiencies if compared to onshore combined cycle systems. Certainly, due to the reduced available space and the weight constraints, combined cycles are not commonly considered as cogeneration systems on conventional offshore petroleum platforms. However, more stringent environmental policies for the natural gas and oil production activities have motivated the integration assessment of advanced technological solutions that aim to mitigate the environmental impact that conventional offshore platforms are responsible for. Accordingly, in this paper, the effect of the integration of a low emission, oxyfuel gas turbine cycle is analyzed and compared against an amines-based post-combustion system and a conventional offshore petroleum platform operation in terms of its exergy efficiency and reduced atmospheric CO2 emissions. Indeed, although the conventional configuration is the most efficient, the oxyfuel powered platform configuration presents close power cycle efficiency of 27.10% and the lowest specific CO2 emissions of 0.014 kgCO2 /toil, whereas the amines-based layout provides the best cogeneration efficiency (55.34%) of the advanced configurations. Moreover, an energy integration analysis is performed to identify the heat recovery potential, while the exergy method is used to evaluate and quantify the most critical components that lead to the largest irreversibilities along the primary separation, cogeneration and gas compression systems. As a result, the study points to ways of decarbonizing offshore applications in the oil and gas sector.